(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The study focused on the morphological variability of the koi carp yearling. (Cyprinus carpio haematopterus), an industrially important and new developing fish species in Uzbekistan. Various meristic indicators were studied, revealing specific features: D III-IV 7-8 (mean 8), A III 5-6 (mean 5), 34 - 38 (36) lateral lines of scales, and 18 - 24 (21) ridges on the first gill arch. These indicators give an idea of the unique morphological features of the carp at this stage of development. In addition, the plastic parameters were evaluated both by classical methods of measuring cypress fish and by geometric morphometry. These parameters provide a more detailed picture of the physical characteristics and variations within the koi carp population.